PENYALAHGUNAAN KEWENANGAN PENGURUS DALAM PENGELOLAAN YAYASAN MENURUT UU NO. 16 TAHUN 2001 Jo. UU NO. 28 TAHUN 2004 - Angeline angeline; Bismar Nasution; Windha windha (TRANSPARENCY, 2013)
Foundation is a nonprofit corporation whose purpose on social, humanitarian an religious. Foundation has an organ to manage the foundation. In conducting its activities, the foundation is managed by a board that actively manage the foundation by Indonesia Law No. 16 of 2001 Jo. Indonesia Law No. 28 of 2004 and the Articles of Association of the foundation in order to achive the aims and objectives of the foundation. Board has the duty and authority and resposibility in running the foundation.The authority granted to the foundation’s board is now being abused by the board. Writing method used to compile this paper is the normatif juridical approach, with an analysis of the problems from the approach to the principles of law and refers to the legal norms contained in the legislation. The research was carried out with an emphasis on the data library by library research such as legislation readings, books, papers, magazines an the internet. Abuse of authority in the management board on this foundation may result in losses as well as the other foundation. In the Law Foundation and the foundation’s articles of association have set about authorty board of trustee. There are restrictions that must be adhered to by the board.   Kata Kunci : Penyalahgunaan, Kewenangan, Pengurus, Yayasan.